Akkad Dynasty Inscriptions from Nippur - Goetze, Albrecht
1. Rīmuš: 5N-T567; 6N-T1033a; 6N-T1033; 2N-445; 6N-T264 (now NBC 10736); 2. Narām-Sīn: 6N-128; 3. Šar-kali-Šarrī: 6N-T1123; 6N-T658; 6N-T112 (now NBC 10619) and 6N-T662.